Camel Production and Management Systems in Different Agro-ecological Zones of Rajasthan - Bhakat, Champak; Chaturvedi, D; Sahani, M S (Annals of Arid Zone, 2016)
Â A study was conducted on various aspects of camel production andmanagement systems in two agro-ecological zones of Bikaner and PalL In a camelherd average representation of I to 4 year age group of camels was found tobe less at Pali as compared to Bikaner district. The above 4-yearcage group femalecamels formed maximum percentage in a herd of both the regions. Bikaner regionwas dominated by camel user (79.33%), where as in Pali district camel breedersformed the major group (65.33%). The main purpose of camel rearing was cartingin Bikaner and trading in Pali district. The purpose of camel rearing significantly(P